SAINT THOMAS AQUINAS AND THE INDIAN VEDANTISTS ON MYSTICISM, SALVATION AND HEAVENLY EXISTENCE: . - Stavig, GopaJ (Journal of Dharma, 2002)
The purpose of this essay is to compare the Christian philosophy of Saint Thomas Aquinas (1225-74) with the religious doctrines of the Indian Vedantists. For each separate topic, the opening statement is made by Thomas Aquinas, followed by the teachings of the traditional Vedantists Shankara (6881788-720/820), Ramanuja (10] 7-1137) and Jiva Goswami (d. 1566), and the modem Neo-Vedantists Swami Vivekananda (1863- 1902), Swami Abhedananda (1866-1939) and Sri Aurobindo (1872- 1950).1